(untitled) (KYAMC Journal, 2025)
Background: Multidetector computer tomography (MDCT) is the most widely used diagnostic modality for routine evaluation of loco-regional involvement and distant metastasis of disease. In this study we evaluate the role of MDCT in the assessment of parametrial involvement in cervical malignancies. Objective: The objective of our study was to prospectively evaluate MDCT criteria for differentiating a cervical cancer confined to the cervix from a lesion that invades the parametrium. Materials and Methods: The clinical records of 130 patients with newly diagnosed, untreated cervical cancer were prospectively studied who met the study requirements were reviewed for this study. Clinical stage was based on the International Federation of Gynecology and Obstetrics (FIGO) staging classification. All patients were pathologically proven. MDCT was done to evaluate loco-regional involvement and distant metastasis of disease. 55 patients had extensive loco-regional involvement and distal metastasis. These 55 patients were excluded from study. Rest 75 cases were underwent radical hysterectomy or Wertheim operation. After the operation, the specimens sent for histological confirmation and the correlation between the CT scan findings of the parametrium and the histopathology result was studied. Result: The sensitivity and the specificity of CT scan in assessing parametrial involvement was 66.7% and 92.2%, respectively. Conclusion: In cervical cancer, MDCT gave better results in staging of advanced cases as well as early-stage ones. Local staging was improved by the acquisition of post-contrast delayed scans. KYAMC Journal Vol. 16, No. 01, April 2025: 24-29